Proses Pembuatan Alat Sandblasting Portable untuk Diaplikasikan pada Komponen Permukaan Logam Karat - Saputra, Muhammad Aji Saputra Aji; Dewi Anjani, Ratna; Kardiman (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Sandblasting is a process for cleaning the surface of contaminated materials such as rust, salt, oil, paint and to obtain material profile characteristics to either roughen or smooth, where this process is often found in manufacturing companies. The sandblasting process is carried out by shooting abrasive material with high air pressure onto the metal surface so that that the dirt stuck to it will be eroded. Several methods can be used for cleaning metal surfaces, such as brushing with a wire, immersion in an acid solution, or with spraying solid particles in the form of sand as an abrasive substance or called sandblasting. This research design uses SS400 carbon steel material and makes a cabin using Galvanized Plate. The study results show that it can provide benefits in the process, and increase insight into how sandblasting equipment technology can be developed in the future.